A Visualization of Fisher's Least Significant Difference Test (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2013)
When a hypothesis of the equality of several means is tested by using ANOVA and it is rejected for a given level of significance, Least Significant Difference (LSD) test is most commonly applied to know which mean(s) is(are) significantly different from which. This procedure usually becomes lengthy. To overcome this situation, a new visualization of LSD test is proposed in this article. This graphical form provides a quicker and clearer picture of the least significant difference test. It is an objective approach when the difference between means is approximately equal to the LSD. Short listing of experimental treatments becomes quite easy by this visualization.